Analisis Clash Detection Pekerjaan Struktur Menggunakan Building Information Modelling Pada Proyek Konstruksi X - Nofriadi; Mizanuddin Sitompul; Rhini Wulan Dary; Citra Utami; Harfa Sakri (Jurnal Konstruksi, 2026)
Conventional Quantity Take-Off (QTO) methods face several significant challenges, particularly in structural projects with complex details and a high variety of elements (columns, beams, slabs, foundations). The limitations of 2D drawing visualization make it difficult to interpret structural details and ensure that no elements are omitted or double-counted. One of the common issues in construction projects is the occurrence of clashes between different work elements, such as structural, architectural, mechanical, electrical, and plumbing (MEP) systems. If not detected early, these clashes can lead to project delays, cost overruns (rework), and even a decline in building quality. The construction project under study is a two-story building designed as an office building. As a case study in this research, this building is expected to provide a realistic picture of potential clashes and how BIM is implemented. Based on BIM-based QTO calculations that account for the impact of clashes at beam-column intersections, the resulting values are lower than those from BIM-based QTO calculations that do not account for such clashes. There is a significant difference in concrete work for column and beam elements. The total cost savings amount to Rp14,126,400.00 when accounting for the impact of clashes at the intersections of columns and beams.